Labyrinthine Enhancement on 3D Black Blood MR Images of the Brain As an Imaging Biomarker for Cisplatin Ototoxicity in (Lung) Cancer Patients - Veiga, M (2020)
Purpose: Cancer patients treated with platinum-based chemotherapy can present with ototoxicity symptoms. The purpose of this work is to report the imaging features related to cisplatin ototoxicity. Methods: Between December 2015 and March 2019, a cohort of 96 consecutive patients with lung cancer was selected. Only patients who received cisplatin chemotherapy and underwent an imaging protocol consisting of a Gd-enhanced 3D-BB and 3D-T1W sequence, as well as T2W sequence to exclude metastases, were included. Labyrinthine enhancement was assessed, and all findings regarding the auditory and vestibular function were retrieved from the clinical files. Results: Twenty-one patients met the inclusion criteria. The Gd-enhanced 3D-BB images were used to divide them into the labyrinth enhancement group (LEG) and the labyrinth non-enhancement group (LNEG). None of these patients demonstrated enhancing regions on the 3D-T1W images. The labyrinthine fluid remained high on the T2 images in all patients, excluding metastases. The LEG consisted of 6 patients. The cochlea and semicircular canals were the most frequently affected regions. All the LEG patients that presented with hearing loss (4/6) had cochlear enhancement. Patients with normal hearing had no cochlear enhancement. Five patients (5/6) showed vestibular enhancement. Four of these patients had vestibular symptoms. Conclusion: Labyrinthine enhancement as an imaging feature related to cisplatin ototoxicity is unreported. This study demonstrates a correlation between hearing loss and cochlear enhancement and also between vestibular impairment and vestibular/semicircular enhancement on 3D-BB images, which remained invisible on the 3D-T1W images. The labyrinthine enhancement on 3D-BB images in the presence of normal signal intensity of the intralabyrinthine fluid can be used as an imaging biomarker for cisplatin toxicity in daily clinical practice and should not be mistaken for intralabyrinthine metastases.